Efficiency of shaping of body balance maintenance ability in year cycle in dance sport athletes on the beginning stage of training process - Zabrocka, A.; Kruczkowski, D.; Dancewicz, T. (World Congress of Performance Analysis of Sport VIII, 2008)
From this study we see that year training cycle in dance sport caused significant increase in the level of body balance maintenance ability of young children. Young dance sport athletes on the beginning stage of training process significantly improved the level of body balance maintenance ability. It should be concluded that training process in dance sport allowed on the effective improvement of the body balance maintenance ability of the researched dancers. Differential level of this ability after one year of training process have been revealing more homogenous character with small individual differences. Next stage of the researches will allow to exclude influence of the factors from the ontogenesis sphere. Training process in dance sport causes the improvement of the body balance maintenance ability level in young dancers on the beginning training stage. In the next researches it is required to concentrate on the demarcating ontogenesis influence and training process on body balance maintenance ability development.